2018
DOI: 10.2495/sdp-v13-n3-436-444
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for water mitigation options using MCDA: A case study in the Galapagos islands

Abstract: Lately, due to overutilization of scarce natural resources such as water, tourist islands have been severely threatened. This is also the case in Santa Cruz Island, the main inhabited island of the Galápagos Archipelago. Therefore, a Multi-Criteria Decision Analysis (MCDA) was carried out with the aim of mitigating the future water crisis. The proposed solutions were evaluated in terms of environmental, technical, economic and social criteria. The results indicate that the 'best' alternative for municipality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Regarding MCA to compare hydraulic structures, researchers such as Loc et al ( 2017 ) compared alternatives for integrated urban water management. Peters et al ( 2019 ) selected the best potable water sources, and Reyes et al ( 2018 ) compared alternatives to water mitigation. Despite the extended application of MCA in water management, only two studies were found that used this method to compare RWHS options: Hämmerling et al ( 2020 ) compared different RWHS for urban areas in Poland suburbs, and Melville-Shreeve et al ( 2016 ) selected RWHS in an urban area in a developed country.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding MCA to compare hydraulic structures, researchers such as Loc et al ( 2017 ) compared alternatives for integrated urban water management. Peters et al ( 2019 ) selected the best potable water sources, and Reyes et al ( 2018 ) compared alternatives to water mitigation. Despite the extended application of MCA in water management, only two studies were found that used this method to compare RWHS options: Hämmerling et al ( 2020 ) compared different RWHS for urban areas in Poland suburbs, and Melville-Shreeve et al ( 2016 ) selected RWHS in an urban area in a developed country.…”
Section: Introductionmentioning
confidence: 99%